m)
2 + ( 3 x 4 : 6 x 50 - 50) + ( 50 :10 x 6 : 3 + 20)= 82
= 2 + ( 12 : 6 x 50 - 50) + ( 5 x 6 : 3 + 20 ) =
= 2 + ( 2 x 50 - 50) + ( 30 : 3 + 20) =
= 2 + ( 100 - 50) + ( 10 + 20) =
= 2 + 50 + 30=
= 82
o)
25 x (160 - 30 x 5) - 8 - ( 24 + 6 : 6) = 217
= 25 x ( 160 - 150) - 8 - ( 24 + 1 ) =
= 25 x 10 - 8 - 25 =
= 250 -8 - 25 =
= 242 - 25 =
= 217
p)
( 600 - 393 ) x 350 - 87 x (29 743 : 49) = 10 326
= 207 x 350 - 87 x 607 =
= 63 135 - 52 809 =
= 10 326
q)
84 x 10 : ( 5 x 84 - 120 x 3 - 54 ) = 140
= 840 : ( 420 - 360 - 54) =
= 840 : ( 60 - 54 ) =
= 840 : 6 =
= 140